The Principal's Strategy in Improving Teacher Performance at SD Negeri 13 Tanah Abang - Rastiana Rastiana; Winda Nopriani; Leny Marlina; Asri Karolina (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The principal's role as an educational manager is very important in ensuring that the school he leads has good quality learning. The principal's strategy is one way to improve teacher performance in the learning process. This research is entitled